Peningkatan Kemampuan Bercakap, Membaca dan Menulis Tentang As-Syi’ru Mata Pelajaran Bahasa Arab Melalui Metode Demonstrasi Pada Siswa Kelas XII Agama MAN 2 Probolinggo - Heriadi, Didik; Farid, Edi Kurniawan (LP3M UNZAH GENGGONG, 2022)
Abstract This research is expected to be able to overcome problems that are happening in class and be able to provide new methods of using demonstration methods in learning Arabic. In this case the researcher also pays attention to how the lesson is to be delivered or what method is most appropriate for a lesson. Therefore this study is entitled: Improving the Ability to Speak, Read and Write Arabic Subjects Through Demonstration Methods in Class XII Religion Students of MAN 2 Probolinggo. Mastery of the Arabic language is an important requirement for the success of individuals, society, the Indonesian people in responding to the challenges of the times at the global level. Mastery of Arabic can be obtained through various programs, while formal Arabic learning programs at madrasas are the main means for most Indonesian children. Keywords: Improvement of Speaking Ability, Improvement of Reading Ability, Improvement of Writing Ability, As-Syi'ru, Arabic Lesson, Demonstration Method